1996
DOI: 10.1152/jn.1996.75.3.1013
|View full text |Cite
|
Sign up to set email alerts
|

Errors in the control of joint rotations associated with inaccuracies in overarm throws

Abstract: 1. Accurate overarm throwing requires precise control of joint rotations so that the ball is released at the appropriate time on the appropriate hand trajectory. Inaccuracy in throws, in turn, must result from errors in the control of joint rotations. But do high and low throws result from disorders in the joint rotations that produce the hand trajectory or in those that cause ball release? Are they due to error at a particular joint or to accumulation of errors across a number of joints? The objective was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 0 publications
5
65
1
Order By: Relevance
“…In throwing a ball, for example, there is a delay of a few hundred milliseconds for the ball to reach the target and visual feedback about the accuracy of the throw to reach the nervous system. Nevertheless, the timing of the finger movements controlling the release of the ball can be learned with remarkable precision -a difference of just 10 ms can cause the throw to be too high or too low (Hore et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In throwing a ball, for example, there is a delay of a few hundred milliseconds for the ball to reach the target and visual feedback about the accuracy of the throw to reach the nervous system. Nevertheless, the timing of the finger movements controlling the release of the ball can be learned with remarkable precision -a difference of just 10 ms can cause the throw to be too high or too low (Hore et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The variability in the horizontal position decreased significantly in the stress session, despite a decline in throwing performance. This result is somewhat surprising, because in many studies the consistent release position has been highly correlated with skilled throwing (e.g., Hore et al, 1994Hore et al, , 1995Hore, Watts, & Tweed, 1996;McDonald et al, 1989).…”
Section: Discussionmentioning
confidence: 97%
“…the handpath, which, in turn, was determined by the timing of finger opening. Given that finger opening was not driven by proprioceptive feedback (Hore et al 1999a), we assumed that PIP joint extension was caused by a central command to the finger muscles (Hore et al 1996;Timmann et al 1999). The present results show that this view needs to be modified.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this, it might be expected that throwing inaccuracy would be caused by lack of precision in the timing of the central command to the fingers. Such evidence has been found in overarm ball throwing, where modeling and experimental studies have shown that ball high/ low inaccuracy could be caused by variability in the timing of finger opening on the handpath (Calvin 1983a(Calvin , 1983bChowdhary and Challis 1999;Hore et al 1996). However, in dart throwing, inaccuracy has been associated with errors in hand trajectory speed (Smeets et al 2002).…”
mentioning
confidence: 89%
See 1 more Smart Citation